PREVALENSI PARAMPHISTOMIASIS PADA SAPI BALI DI KECAMATAN LIBURENG, KABUPATEN BONE - Darimin. S P Yulisa. F, Sirupang. M (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. Paramphistomiasis is a disease caused by infection of Paramphistomum sp. The disease can be affecting productivity of Bali cattle. A description study was conducted to determine the prevalence of paramphistomiasis in Bali cattle of Libureng sub-district, Bone regency. Faecal samples were collected from 100 cattle and were selected with proporsional random sampling in each village. Research was done at June 29 until July 16th 2014. Faecal samples were collected from the rectal of Bali cattle in Libureng subdistrict, Bone regency. Faecal were examined by sedimentation method to detect eggs of Paramphistomum sp. on the basis of their morphology. Prevalance was calculated by dividing positive of sample with the total sample of examined then multiplied 100%. The result showed that prevalence paramphistomiasis in bali cattle of Libureng sub-district, Bone regency were 57%.